2021
DOI: 10.1038/s42003-021-02046-9
|View full text |Cite
|
Sign up to set email alerts
|

Pleckstrin-2 is essential for erythropoiesis in β-thalassemic mice, reducing apoptosis and enhancing enucleation

Abstract: Erythropoiesis involves complex interrelated molecular signals influencing cell survival, differentiation, and enucleation. Diseases associated with ineffective erythropoiesis, such as β-thalassemias, exhibit erythroid expansion and defective enucleation. Clear mechanistic determinants of what make erythropoiesis effective are lacking. We previously demonstrated that exogenous transferrin ameliorates ineffective erythropoiesis in β-thalassemic mice. In the current work, we utilize transferrin treatment to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…However, whether increased ROS resulting in apoptosis as the cause of ineffective erythropoiesis has never been definitely confirmed. We and others previously demonstrate that EPO downstream mechanisms are potent anti-apoptotic compensatory mechanisms and that reversal of apoptosis does not ameliorate ineffective erythropoiesis in β-thalassemia [76,77]. Our current results demonstrate borderline increased erythroblast apoptosis while ROS is significantly enhanced in MDS mice and no change in apoptosis while ROS is significantly decreased in DFP-treated MDS mice.…”
Section: Discussionsupporting
confidence: 54%
“…However, whether increased ROS resulting in apoptosis as the cause of ineffective erythropoiesis has never been definitely confirmed. We and others previously demonstrate that EPO downstream mechanisms are potent anti-apoptotic compensatory mechanisms and that reversal of apoptosis does not ameliorate ineffective erythropoiesis in β-thalassemia [76,77]. Our current results demonstrate borderline increased erythroblast apoptosis while ROS is significantly enhanced in MDS mice and no change in apoptosis while ROS is significantly decreased in DFP-treated MDS mice.…”
Section: Discussionsupporting
confidence: 54%
“…PLEK2 binds to membrane‐associated phosphatidylinositol produced by phosphatidylinositol 3‐kinase, which subsequently regulates actin cytoskeleton organization and cell spreading [ 6 ]. Although aberrant expression of PLEK2 has been shown to play a critical role in regulating many important biological processes such as inflammation, erythropoiesis and tumorigenesis [ 7 , 8 , 9 ], its underlying cellular and molecular mechanisms remain poorly understood. PLEK2 was reported to be highly expressed in several malignancies, including non‐small cell lung cancer [ 10 ], gallbladder cancer [ 11 ] and gastric cancer [ 12 ], while low PLEK2 mRNA levels were observed in multiple myeloma bone marrow progenitor cells [ 13 ] and prostate cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DEP domain is in the center, and the two PH domains are in the amino- and carboxyl-terminals, which are important for PLEK2 colocalization with the actin cytoskeleton at the immune synapse and integrin clusters and involve a broad range of cellular functions [ 10 13 ]. Previous studies have shown that PLEK2 regulates actin dynamics and cofilin's mitochondrial localization during erythropoiesis [ 14 , 15 ]. PLEK2 induces lamellipodia formation depending on its DEP domain.…”
Section: Discussionmentioning
confidence: 99%